A Public Faith—but for Everyone and Every Public?. Issue 6 (1st January 2013) - Stackhouse, John G.
Abstract: Miroslav Volf's sets out a strong, good thesis about the freedom religious people ought to have to participate in public as fully themselves, as religious people. This thesis is in tension with the fact that some people seek to harm others, or to radically compromise public life itself, in the name of their religion. Along the way, Volf makes a number of points that seem puzzling, at least overstated, but perhaps even incoherent with other claims he makes or with data that he likely also knows. I raise the possibility that the author's social location may help to explain at least some of these debatable features of his otherwise salutary book.